The Civil Counterfeiting Suit A Comparative Analytical Study - Hussein, Sarkaut Ismail (Journal of Legal and Political Studies, 2017)
"The Civil counterfeiting suit ""A Comparative Analytical Study"" The allegation of counterfeiting is the set of procedures provided by the law to prove the validity of the bonds, and may be set up in the original before a competent civil court by a person invoked by a bond or filed in an original civil or criminal suit. In some cases, however, a genuine civil counterfeiting suit must be filed by the plaintiff to judge the counterfeiting of the bonds. The Iraqi legislator, contrary to the position of some legislation, did not strictly regulate the provisions of the civil counterfeiting suit and dealt with the issue in a way that is not free of ambiguity and wear, so that it did not regulate the manner of submission, the procedures to be followed and the consequences thereof, and how jurisdiction the civil court to investigate the allegation counterfeiting"
Keywords: Validity; Criminal suit; Iraqi legislator; jurisdiction